The aging hematopoietic stem cell niche: a mini review - Gao, Xin; Zhang, Jing; Tamplin, Owen J. (Frontiers in Hematology, 2025)
Hematopoietic stem cells (HSCs) undergo a functional decline during aging. The intrinsic characteristics of aged HSCs have been well-described and include a strong myeloid bias, an increase in total number, and a decrease in functionality during transplantation. The impact of the aged bone marrow microenvironment, or niche, on HSCs is less well understood. It is critical to understand the changing condition of the niche during aging, and its ability to support HSCs, as this could reveal the very signals and mechanisms needed to improve HSC fitness. Furthermore, heterochronic transplantation provides an approach to test the influence of an aged recipient niche on young donor HSCs, and conversely, of a young recipient niche on aged donor HSCs. Importantly, these experiments demonstrated that donor HSC engraftment is reduced if the recipient niche is aged, and conversely, the young niche can rejuvenate aged donor HSCs. Here we will focus on the interactions between aged HSCs and their microenvironment. We will highlight current controversies, research gaps, and future directions.